Indoor and outdoor culture of Spirulina (Arthrospira platensis) grown in different salinity in Sultanate of Oman - Ali Saif, Almahrouqi Hafidh (2017)
Oman is in semi-arid and arid region, which receive extremely high light intensity and limited rainfall annually. Dry weather condition has caused diminishing underground water resources and has lead to seawater intrusion problems. This study is to explore the potential of Spirulina (Arthrospira platensis) that can be used to be cultured as a solution to the seawater intrusion. Most crops depend on freshwater or underground water resources, however Spirulina has the ability to grow and adapt to high saline condition. The experiment was conducted in the Agricultural Experimental Station of Sultan Qaboos University, Muscat, Oman. Result of the study concluded that with sufficient acclimatization, Spirulina can be grown in salinity ranges from 10 to 40 psu without having large differences of dry weight biomass, biochemical composition and fatty acid profile. In this study, Spirulina cells have produced the highest dry weight (g L-1) to 10 psu in ten days of average at 0.506 ± 0.039. Carbohydrates are the highest (27.29 ± 0.518) and high protein (%) also can be produced by Spirulina cultured with 10 psu in the external environment (outdoor), in which lipid and ash content (%) is low were produced. However, the amount of SAFA, MUFA and PUFA (% dry weight) obtained with 10 psu did not differ significantly (p <0.05) than other salinity concentration. The market price for Spirulina is extremely high compare to the fruits and vegetables, farmers in Oman will consider these types of cultivation as the best solution for them farming salinity problems whatever the percentage of the salinity was in their farm. At the same time, the government may take this opportunity to move part of the recruitment pressure for those who lost their farm because of the salinity intrusion by providing better solution. Spirulina farming will create so many good benefits to the country.